Biosythesis of Silver Nanoparticles using Putri Malu (Mimosa pudica) Leaves Extract and Microwave Irradiation Method - Is Fatimah; Nur Afisa Lintang Mutiara (Molekul, 2016)
In this paper, the biosynthesis of silver nanoparticles (AgNPs) using Mimosa pudica extract is discussed. Mimosa pudica leaves extract using water as solvent was used as bio-reductor to an aqueous solution of silver nitrate (AgNO3) and in order to accelerate the reduction, microwave irradiation method was applied. The AgNPs obtained were characterized using UV-Vis spectrophotometry, FTIR spectrophotometry, XRD, SEM-EDX, and particle size analysis based on dynamic scattering method. Effect of preparation method to the formation of AgNPs is also evaluated in antibacterial activity towards E.coli and P. aeruginosa. Rapid and ecofriendly biosynthesis of stable silver nanoparticles was observed in this study. The characterization results and antibacterial assay indicated the uniform and smaller particle size of AgNPs obtained by using microwave method and positively enhance the antibacterial activity against tested bacteria.